UTILIZATION OF MORINGA LEAVES (Moringa Oleifera) AND LAMTORO LEAVES (Leucaena Leucocephala) AS RAW MATERIALS FOR MAKING LIQUID ORGANIC FERTILIZER (LOF) - M Yunus; Muhammad Danda Saputra; Reza Fauzan (Politeknik Negeri Lhokseumawe, 2026)
This study aims to utilize Moringa leaves (Moringa oleifera) and Leucaena leucocephala leaves (Leucaena leucocephala) as raw materials for making environmentally friendly liquid organic fertilizer (POC). This study examines the effect of the composition of raw materials of Moringa leaves and Leucaena leucocephala leaves, as well as fermentation time on the quality of the resulting POC, which is tested based on parameters of pH, Total Dissolved Solids (TDS), macronutrient content (nitrogen, phosphorus, potassium), and C-organic content. This study was conducted with variations in the composition of Moringa leaves and Leucaena leaves at a ratio of 1:0, 3:1, 1:1, 1:3, and 0:1, as well as varying fermentation times for 7, 12, 17, 22, and 27 days. The results of the study showed that the combination of Moringa leaves and Leucaena leucaena leaves at a ratio of 1:1 and fermentation for 17 days produced POC with optimal nutritional content, namely Nitrogen (0.31%), Phosphorus (0.17%), Potassium (0.25%), and C-organic (0.42%). In addition, this study also showed that fermentation time had a significant effect on the quality of POC, with an increase in POC quality on the 17th day of fermentation. The results of this study can be used as an alternative in making liquid organic fertilizers with local, environmentally friendly raw materials, as well as contributing to sustainable agriculture through the use of more efficient and affordable fertilizers. Keywords: Liquid Organic Fertilizer, Moringa Leaves, Leucaena Leaves, Fermentation, Plant Nutrition.